Multi Scale Numerical Modelling Related to Hydrofracking for Deep Geothermal Energy Exploitation. (2016) - Insana, Alessandra; Barla, Marco; Elmo, Davide
Abstract: Prediction of fracture propagation through rock masses is investigated in this paper by adopting the Distinct Element Method (DEM) and the Voronoi tessellation. A microstructure-based model was created. Microparameters governing Voronoi sub-blocks contacts behaviour were calibrated against laboratory tests results for different rocks. An upscaling procedure is proposed to build reliable and representative numerical models at in situ scale to study fracture propagation for deep geothermal wells.